In vitro Investigation of Radiotherapy along with Gemcitabine Loaded PEG Gold Nanoparticles Against MCF-7 Breast Cancer Cells - Ali Salarvand; Ahmad Shanei; Seyed Hossein Hejazi; Iraj Abedi; Neda Attaran Kakhki (Advanced Biomedical Research)
Background: Breast cancer is one of the major causes of cancer death in women. Usually, surgery, chemotherapy, and radiotherapy are commonly used in the treatment of breast cancer, but these methods have significant side effects and low survival rates. By developing combination therapies, side effects can be reduced so that therapeutic efficacy is maintained. The aim of this study was to examine the effects of radiotherapy combined with chemotherapy using combined gem and gold nanoparticle for the treatment of breast cancer. Materials and Methods: In this study, PEGylated gold nanoparticles (PEG-GNPs) were synthesized and loaded with an anticancer agent, gemcitabine (Gem-PEG-GNPs). Then, GNPs, PEG-GNPs, and Gem-PEG-GNPs were investigated using several techniques, including UV-Vis, FTIR, DLS, and TEM analysis. After that, the efficacy of the synthesized nanoparticles for chemoradiotherapy was evaluated through in vitro experiments. Results: The prepared Gem-PEG-GNPs act as radiosensitizers and nanocarrier, which increases the effectiveness of radio chemotherapy and reduces side effects. Combining Gem-PEG-GNPs with X-ray irradiation increased apoptosis and decreased survival rates of MCF-7 cells. When Gem-PEG-GNPs and radiation were combined, a significant synergistic effect was observed compared to the effect of radiation alone. Conclusion: Gem-PEG-GNPs can have the potential of an effective and radiosensitizing drug delivery agent against breast cancer therapeutics.